Developing the Students’ English Listening Skill by Applying Drama Movies Viewing Techniques - Suramto, Suramto (ENGLISH FRANCA : Academic Journal of English Language and Education, 2019)
Listening is one of fundamental skills in English. Unfortunately, most students are not able to achieve listening skill well. There are many factors that influence students? listening skill is low.  This research tried to solve the problem regarding the students' difficulities in achieving listening skills by using drama movies reviewing technique this study is a quasi experimental design. The object of this paper were 30 students' of students of general conversation Classes. The data were collected by using listening achievement test. The results showed that the students who were treated by the techniques of viewing drama movies achieved higher mean score in listening skill (81.46). The techniques of viewing drama movies also gave contribution in listening skill (61.8%).  Keywords: drama movies viewing techniques and listening skill Listening is one of fundamental skills in English. Unfortunately, most students are not able to achieve listening skill well. There are many factors that influence students? listening skill is low.  This research tried to solve the problem regarding the students' difficulities in achieving listening skills by using drama movies reviewing technique this study is a quasi experimental design. The object of this paper were 30 students' of students of general conversation Classes. The data were collected by using listening achievement test. The results showed that the students who were treated by the techniques of viewing drama movies achieved higher mean score in listening skill (81.46). The techniques of viewing drama movies also gave contribution in listening skill (61.8%).  Keywords: drama movies viewing techniques and listening skill